Hitchhiking motility of Staphylococcus aureus involves the interaction between its wall teichoic acids and lipopolysaccharide of Pseudomonas aeruginosa - Liu, Chao-Chin; Lin, Mei-Hui (Frontiers in Microbiology, 2023)
Different bacteria are known to cooperate in an ecosystem for survival. Staphylococcus aureus, which lacks pili and flagella, is a nonmotile microorganism; it uses a mode of migration called alternative spreading by interacting with flagellated Pseudomonas aeruginosa to move in the environment. This study demonstrates that the alternative spreading of S. aureus is mediated through the interaction between lipopolysaccharide (LPS) of P. aeruginosa and wall teichoic acid (WTA) of S. aureus. The alternative spreading of S. aureus SA113 decreases upon deletion of tagO, which encodes the enzyme TagO required for WTA synthesis. However, when a tagO deletion mutant of S. aureus SA113 was transformed with a plasmid expressing TagO, this alternative spreading is restored. Flow cytometry analysis also shows that LPS of P. aeruginosa is involved in facilitating the movement of S. aureus. We observed that P. aeruginosa facilitates the movement of S. aureus inside the digestive tract in a Caenorhabditis elegans model. The interaction between moving P. aeruginosa and the attached S. aureus was observed under a fluorescence microscope. We also demonstrate this alternative movement in mice using an in vivo imaging system (IVIS). In conclusion, this study elucidates how S. aureus gains alternative motility by hitchhiking on moving bacteria in the same ecosystem. The results derived from this study improve our understanding of how this nonmotile pathogen moves in the environment and spreads in human tissues to cause diseases.